Pengaruh Harga dan Kualitas Produk terhahap Keputusan Pembelian - Pasaribu, Samuel Sahat Maruli; Hidayat, Agus Maolana (Jurnal Informatika Ekonomi Bisnis, 2023)
The beverage industry market in Indonesia has developed from year to year, which has prompted several manufacturers to be increasingly interested in companies engaged in the beverage industry, one of which is Chatime and Koi The. Chatime and Koi The have opened many branches of their company in several areas, including one in Bandung. The large number of enthusiasts for the bubble tea drink has pushed the Chatime and Koi The companies to compete to make efforts for consumers to continue buying their products. The purchase decision is also influenced by several factors, one of which is the price factor and also the product quality of these beverage products. The main objective of this study was to determine the effect of price and product quality on purchasing decisions for Chatime and Koi the in Bandung. This type of research used is a quantitative method. The sampling technique used is non-probability sampling with type purposive sampling. A total of 100 questionnaires were collected and analyzed using multiple linear regression using Statistical Product and Service Solutions (SPSS) Version 26. The results of the study show that price and product quality partially or simultaneously have a significant effect on Chatime purchasing decisions, while partially product quality has a significant effect on purchasing decisions for Koi The products in Bandung and the price variable has no significant effect. However, the simultaneous price and product quality have a significant effect on purchasing decisions for Koi the in Bandung.